1992
DOI: 10.1128/aac.36.3.558
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of sparfloxacin compared with those of five other quinolones

Abstract: The in vitro activity of sparfloxacin, a new difluorinated quinolone, was evaluated against 857 gram-positive and gram-negative clinical isolates and compared with those of ciprofloxacin, norfloxacin, ofloxacin, fleroxacin, and lomefloxacin. The MIC of sparfloxacin for 90%o of the members of the family Enterobacteriaceae tested was 0.5 ig/ml (range, 0.06 to 4.0 uig/mI); only for members of the genera Serratia,-Citrobacter, and Providencia were MICs above 1 ug/mL. Some 90% of Pseudomonas aeruginosa isolates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 15 publications
0
36
1
Order By: Relevance
“…Widely-used fluoroquinolones, such as ciprofloxacin and ofloxacin, have excellent activity against Gram-negative pulmonary pathogens, but they have only marginal activity against S. pneumoniae with the minimal concentration required to produce 90% inhibition (MIC90s) ranging 1-4 mg·L -1 compared to MIC90s of <0.5 mg·L -1 for most of the Gram-negative pathogens [1,2,6]. Clinical studies have shown ciprofloxacin and ofloxacin to have good clinical efficacy in the treatment of bronchopulmonary infections due to S. pneumoniae [35], but other investigators have reported low clinical success rates with a high rate of persistence of S. pneumoniae after therapy [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Widely-used fluoroquinolones, such as ciprofloxacin and ofloxacin, have excellent activity against Gram-negative pulmonary pathogens, but they have only marginal activity against S. pneumoniae with the minimal concentration required to produce 90% inhibition (MIC90s) ranging 1-4 mg·L -1 compared to MIC90s of <0.5 mg·L -1 for most of the Gram-negative pathogens [1,2,6]. Clinical studies have shown ciprofloxacin and ofloxacin to have good clinical efficacy in the treatment of bronchopulmonary infections due to S. pneumoniae [35], but other investigators have reported low clinical success rates with a high rate of persistence of S. pneumoniae after therapy [36].…”
Section: Discussionmentioning
confidence: 99%
“…Excellent in vitro activity, improved pharmacokinetic properties, the possibility of single daily dosing and the increased half-life of sparfloxacin as compared with the fluoroquinolones available at present makes it a suitable candidate for the treatment of lower respiratory tract infections [1,47,48]. However, the indication for treatment with sparfloxacin will have to be decided with care, because of some toxicological problems, such as photosensivity and Qtc interval prolongation [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing resistance of X. maltophilia to the commercially available quinolones is worrisome and requires further investigation (3, 4, 10, 12, 16, 17, 21-23, 30, 33). Although the investigational quinolones show good in vitro activity compared with that of ciprofloxacin and other quinolones (3,13,17,19,21,22,29,30,32,33), their clinical usefulness needs to VOL. 38,1994 on be determined after further in vitro investigation of, for example, their stability to selection of resistant strains.…”
mentioning
confidence: 99%
“…DU-6859a (DU) is a new fluoroquinolone antimicrobial agent with the chemical structure 7-[(7S)-7-amino-5-azaspiro [2,4]heptan-5-yl]-8-chloro-6-fluoro-1-[(lR,2S)-2-fluoro-1-cyclopropyl]-1,4-dihydro-4-oxo-3-quinolinecarboxylic acid sesquihydrate (25). Since the presently available fluoroquinolone agents possess only moderate activities against many gram-positive bacteria, recent efforts have been directed toward the synthesis of compounds which have greater activities against these organisms, such as tosufloxacin (1), sparfloxacin (1,3,9), CI-934 (4), WIN 57273 (7,15,17), PD 117596 (5), PD 127391 (CI-960) (5,9,20), PD 131628 (9), T-3761 (10), OPC-17116 (14), AM-1155 (13), E-4497 (11), CP-74667 (16), and CP-99219 (6). DU appears to be one of the most active of these agents (25).…”
mentioning
confidence: 99%